Parents’ perceptions of food intolerance among under-five children in Gianyar Bali - Endy P Prawirohartono; Ni Made Yuni Gumala (Paediatrica Indonesiana, 2003)
Objective To estimate the proportion of food intolerance in chil-dren based on parents’ perception and to analyze factors associ-ated with food elimination.Methods A cross-sectional study was done among 250 mothersof under-five children in Gianyar District, Bali. Mothers were inter-viewed with a questionnaire concerning basic characteristics ofthe children, the family, a list of allergic diseases, disturbance afteringesting certain foods, food avoidance, the reason for eliminatingcertain foods, the person who gave advice, and probable parentalhistory of allergic diseases.Results Fifty-three children (21.2%) were suspected to have ‘prob-able allergic diseases’ and six (2.4%) had ‘probable food intoler-ance’. Food elimination was practiced in 27 (10.8%) families. ‘Prob-able allergic parents’ was found in 49 (19.6%) families. There wasa significant difference in child allergy in proportion to parentalallergy (x 2 test p<0.0001). Food elimination was not associatedwith parental allergies, children’s allergies or children’s ages (x 2test p=0.36, 0.47, and 0.56), but seemed to be related to loweducational status of mothers (x 2 test p<0.0001) and fathers(Fisher’s exact tests p< 0.0001).Conclusions The proportion of children with ‘probable allergic dis-eases’ was higher in families with ‘probable allergic parents’. Theproportion of food elimination was greater than the prevalence of‘probable food intolerance’. Low educational status of parentsplayed an important role in this discrepancy of food elimination inchildren